Women in Union Leadership: A case study of the Ghana Public Service Workers’ Union (PSWU. - Eva, Oteng (University of the Witwatersrand, Johannesburg, 2023)
This research examines the extent to which affirmative policies (gender mainstreaming, gender equality) lead to substantive improvements in the position of women within the Public Services Workers Union (PSWU) in Ghana. The research data for this study was collected using two methods: An online survey that focused on the experience and perceptions of 46 women leaders in the National Executive Council (NEC). The research is a mixed method in the sense that it generated both qualitative and quantitative data. Semi-structured interviews online with 7 key stakeholders, including women and men, in the national office. Data was triangulated to deal with issues of validity and reliability. Analysis is framed under how the equality plan has been implemented in PSWU and the challenges in terms of women’s leadership efforts in decision-making. It was observed that improvement in women participation in the union is because of gender mainstreaming policy and interventions. This proves an argument in a similar study by Britwun et al (2014) that when women are significantly represented in leadership especially in the mainstream there is a possibility of achieving negotiations for women related issues that is perceived as cost to the organisation. This cost includes childcare facilities and additional maternal/paternal leave (Britwum et al 2014). The survey also projects that there are women leaders who play double roles in the union and at home which affects performances and contributions to union affairs as stated by Kirton and Healy (2008,4) in their research stated that “paid work and work in the home constitute a ‘double burden’ and trade union participation (and other such voluntary activities) adds another ‘burden’ for many women''. The trend of domestic or household responsibilities should be carefully studied and used as a tool to address the issue of women’s lack of interest and commitment to union activities and other leadership roles. iii In this regard, increase in women's representation increases women’ consciousness about their demands and strives to realize them.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Arts in Labour Policy and Globalization to the Faculty of Humanities University of the Witwatersrand, Johannesburg, 2024
Keywords: Affirmative policies; Gender mainstreaming; Gender equality; Public Services Workers Union (PSWU); Women in leadership; Ghana Women’s participation National Executive Council (NEC); UCTD; SDG-5: Gender equality